2019
DOI: 10.1371/journal.pone.0227031
|View full text |Cite
|
Sign up to set email alerts
|

The role of gadolinium in magnetic resonance imaging for early prostate cancer diagnosis: A diagnostic accuracy study

Abstract: ObjectiveProstate lesions detected with multiparametric magnetic resonance imaging (mpMRI) are classified for their malignant potential according to the Prostate Imaging-Reporting And Data System (PI-RADS™2). In this study, we evaluate the diagnostic accuracy of the mpMRI with and without gadolinium, with emphasis on the added diagnostic value of the dynamic contrast enhancement (DCE).Materials and methodsThe study was retrospective for 286 prostate lesions / 213 eligible patients, n = 116/170, and 49/59% mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…After the second dynamic phase of dynamic contrast-enhanced scanning, the contrast agent GD DTPA was injected through elbow vein with high-pressure syringe at the injection rate of 2 ml/s and the dose of 0.2 mmol/kg, and then, 20 ml normal saline was injected intravenously at the same rate [ 16 ] Image analysis method SWI image processing and analysis: two senior doctors in the imaging department of our hospital jointly evaluate the film. Their opinions are not unified at one time, and a unified opinion is reached through negotiation [ 17 ]. According to the SWI image obtained by the patient, the internal bleeding focus of the focus was evaluated by SUSE score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the second dynamic phase of dynamic contrast-enhanced scanning, the contrast agent GD DTPA was injected through elbow vein with high-pressure syringe at the injection rate of 2 ml/s and the dose of 0.2 mmol/kg, and then, 20 ml normal saline was injected intravenously at the same rate [ 16 ] Image analysis method SWI image processing and analysis: two senior doctors in the imaging department of our hospital jointly evaluate the film. Their opinions are not unified at one time, and a unified opinion is reached through negotiation [ 17 ]. According to the SWI image obtained by the patient, the internal bleeding focus of the focus was evaluated by SUSE score.…”
Section: Methodsmentioning
confidence: 99%
“…Image analysis method SWI image processing and analysis: two senior doctors in the imaging department of our hospital jointly evaluate the film. Their opinions are not unified at one time, and a unified opinion is reached through negotiation [ 17 ]. According to the SWI image obtained by the patient, the internal bleeding focus of the focus was evaluated by SUSE score.…”
Section: Methodsmentioning
confidence: 99%
“…Recent literature indeed focuses on the overlapping diagnostic validity using bp and mp protocols in detecting csPCa (62).…”
Section: Biparametric Mri (Bpmri) Vs Mpmrimentioning
confidence: 99%
“…Evidence from a study has shown that PI‐RADS, even with shortened imaging sequences, can provide high negative predictive value in lesions with a score of 1–2 and high positive predictive value in lesions with a score of 4–5 16 . Therefore, application of biparametric (Bp) MRI by omitting DCE imaging was recently proposed 17,18 . The results have demonstrated that Bp‐MRI does not compromise the detection of harmful disease and increases MRI capacity at lower direct costs when compared with Mp‐MRI 19 .…”
mentioning
confidence: 99%
“…The results have demonstrated that Bp‐MRI does not compromise the detection of harmful disease and increases MRI capacity at lower direct costs when compared with Mp‐MRI 19 . However, omitting DCE may increase the risk of missing clinically significant disease, especially in PI‐RADS 3 findings in the peripheral zone 18,20 . Recently, it was suggested that Bp‐MRI should not be applied routinely and should be reserved for experienced expert centers only 21 .…”
mentioning
confidence: 99%